2020
DOI: 10.1108/pr-06-2020-0492
|View full text |Cite
|
Sign up to set email alerts
|

Does person–organization spirituality fit stimulate ethical and spiritual leaders: an empirical study in Jordan

Abstract: PurposeThis paper emphasizes the theoretical relevance that workplace spirituality may add to the person–organization (P-O) fit theory through the examination of a framework that comprises how workplace and self-spirituality fit enhances the perceived P-O spirituality fit. A related aim is to test how the perceived P-O spirituality fit enhances both employees' ethical and spiritual leadership behavior.Design/methodology/approachData were collected using a quantitative study of 132 employees across various orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Further, such leaders who follow moral principles and possess strong personal ethics are likely to be viewed as moral role models by their followers (Comer and Vega, 2011). Koburtay and Haloub (2020) argued that spiritually inclined organizations enhance the ethical and spiritual leadership behaviors. Besides, IJCHM 34,10 spiritually inclined individuals and organizations have aligned values framework (Milliman et al, 2003;Ashmos and Duchon, 2000), striving for a high sense of ethics and integrity to make a valuable contribution to the larger society.…”
Section: Discussionmentioning
confidence: 99%
“…Further, such leaders who follow moral principles and possess strong personal ethics are likely to be viewed as moral role models by their followers (Comer and Vega, 2011). Koburtay and Haloub (2020) argued that spiritually inclined organizations enhance the ethical and spiritual leadership behaviors. Besides, IJCHM 34,10 spiritually inclined individuals and organizations have aligned values framework (Milliman et al, 2003;Ashmos and Duchon, 2000), striving for a high sense of ethics and integrity to make a valuable contribution to the larger society.…”
Section: Discussionmentioning
confidence: 99%
“…The construct of spirituality in the workplace has become a meaningful topic of research in the field of organizational behaviour in the recent past (BENEFIEL e colab., 2014;DREYER e HERMANS, 2014;KOBURTAY e HALOUB, 2022). Although spiritual ideas and beliefs have existed for centuries and even millennia and have been responsible for shaping social value systems around the world, they are still considered alternative paradigms, especially when discussing organizational behaviour (RUPČIĆ, 2017).…”
Section: Spirituality In the Organizationsmentioning
confidence: 99%
“…This is prompted by resource-based and dynamic capability views of the firm, which suggest that having employees act ethically is a potential source of business value. Studies have shown that higher levels of PO fit can be achieved by strengthening the organization's ethical climate (Al Halbusi et al 2020), improving managers' ethical leadership (Al Halbusi et al 2020a, b;Dimitriou and Schwepker 2019), matching employees' and the organization's levels of spirituality (Koburtay and Haloub 2022), making the organization's HRM more socially responsible (Zhao et al 2021), and improving organizational justice (Al Halbusi et al 2020a, b).…”
Section: Contemporary Theme 3: Ethical Considerationsmentioning
confidence: 99%